Entre o fosso e o topo: uma leitura histórica do romance Uma Tragédia Americana, de Theodore Dreiser - Nascimento, João Victor Felix (2024)
This dissertation discusses the novel An American Tragedy, by the American realist writer Theodore Dreiser. The text seeks to understand the way in which the dialog between Literature and History took place at the time in which the writer lived. The analysis of this novel made it possible to discuss and analyze some of the developments in the process of consolidating American capitalism since the end of the 19th century. In particular, we've highlighted how the rapid economic rise motivated mainly by the expansion of industrial capitalism led to a consumer boom in the country. To a large extent, the growth in consumption led society to take on a strongly materialistic character. For these and other reasons, the ambition and desire to reach high levels in the social and economic pyramid accompanied the history of many Americans at the time. We argue that this historical process served as the basis for the construction of the writer's literature. In addition, we realize that the novel can be read as a historical source that speaks to the transformation of the old Protestant ethic into a mentality based purely on consumption and the desire for material possession. The old diligent and frugal behaviors oriented towards spiritual salvation underwent a readaptation, so that their purpose was now the production of wealth. In this sense, this dissertation sought to situate and understand Theodore Dreiser's literature in relation to the historical moment of the turn of the 19th century into the 20th century. Especially in the 1920s, when the novel was written, we can see various historical dimensions portrayed by the writer. Cultural traits, psychological realities, class relations and ideological profiles are some of the elements investigated throughout this work.